Bem-estar subjetivo, resiliência e representações sociais no contexto do diabetes mellitus - Costa, Fabrycianne Gonçalves (2017)
This thesis had as general objective to apprehend the social representations about diabetes and treatment developed by diabetics and to quantify the levels of Subjective Well-being (SWB) and resilience in this group of belonging. To achieve this, it was necessary to develop four studies, presented in the form of articles, three of them based on the Theory of Social Representations and one supported in the SWB and resilience constructs. The article 1 aimed to carry out a systematic review of the diabetes subsidized in the theory of Social Representations. Thus, a bibliographic survey was carried out by means of articles published in the databases GALE, SCIELO, MEDLINE and SCOPUS, between the years 2006 and 2016, using the combinations of descriptors "diabetes and social representations", "diabetes and representações sociais", and "diabetes and representaciones sociales". It was selected 9 articles, the results pointed to four main axes: (i) "Nutritional aspects"; (ii) "Diabetes and their settings"; (iii) "Support of the family members and the health professional" and (iv) "Consequences of diabetes". In short, the common-sense thinking conveyed in the revised articles was consensual about dietary difficulties. Despite the overvaluation of the need for food reeducation, there is a difficulty to its adherence due mainly to the emotional character. Regarding the support of the family and the health professional, it was observed that the overprotection by the first and that the lack of credibility in the medical team can interfere directly in the commitment of adherence to the treatment. The article 2 aimed to apprehend the social representations elaborated by people who have diabetes about the disease. As many as 31 people, with ages ranging from 34 and 76 years old (M = 55.68; SD = 11.6), who responded to a sociodemographic questionnaire and depth interview. The data were submitted to the Alceste software and analyzed using descriptive statistics and lexical analysis. The participants pointed out in their social representations were focused on the ignorance of diabetes, highlighting the surprise of the diagnosis, their representations were also anchored in nutritional and emotional factors which were permeated by negative emotions. Participants who used insulin have ratified responsibilities notions for the consequences of this disease, such as the case of the limbs amputation, those who did not used insulin described the disease linked to the triad of treatment (medication, dietary reeducation and physical activity). The article 3 aimed to analyze the social representations about diabetes mellitus and treatment elaborated by diabetics. The sample was composed of 104 participants with ages between 19 and 79 years (M = 56.16; SD = 13.01), who answered a sociodemographic questionnaire and the Free Word Association Test. The data were submitted to SPSS - 23.0 and Tri-deux-Mots software´s and analyzed using descriptive statistics and factorial correspondence analysis. The results showed that the consensus knowledge about diabetes does not differ from the scholarly knowledge. Regarding conception and treatment, diabetes was represented as a chronic disease related to blood sugar problems, mood swings and danger of life, like scientific knowledge. Treatment emerged in a manner associated to food control, adherence and maintenance of medical guidelines. It was possible to perceive consensual and discourse representations. The first ones concern the control that treatment requires. In the disbursals women focused on the disease associated with food restriction and mood swings and men associated diabetes with blood problems, life-threatening risks that may lead to death, and that they must obey the rules of treatment. The article 4 aimed to analyze the SWB and resilience in people with diabetes mellitus, it was applied the scales of SWB and resilience to 104 diabetic patients with a mean age of 56.16 years (SD = 13.01). The results showed that 65.4% of the participants presented high levels of SWB, with a higher mean for positive affects 3.65 (SD = 0.65); it was observed that most participants had high resilience (87.5%). It was found that the positive affect dimension of the BES scale correlated with the dimensions, actions and values (r = 0.58) and self-confidence (r = 0.23) of the resilience scale.The increase in the experience of positive emotions among the diabetics provided greater acceptance of themselves regarding the disease and its therapeutics. It is hoped that such studies will contribute to the construction of scientific knowledge from the perspective of the diabetic person, as well as to provide greater visibility to the disease regarding the elaboration of therapeutic practices focused on both their physical and emotional aspects.